Multiple Hepatic Abscesses Following Yersinia Enterocolitica Septicemia - Franco Colizza; Serge LePage; Jean-François LaJoie; Raymond Duperval; André Marcoux; Jacques Mongeau; Denis Bergeron (Canadian Journal of Gastroenterology)
Septicemia from Yersinia enterocolitica is unusual. Hepatic involvement occurring in this clinical setting is a rare complication. A case of a 64-year-old man who developed septicemia from Y enterocolitica is reported. Abdominal ultrasound and computerized axial tomography scan revealed multiple defects in liver parenchyma compatible with abscesses. After treatment with intravenous aminoglycosides followed by trimethoprim-sulfomethoxazole, recovery was complete. General considerations regarding the manifestations and pathogenesis of Y enterocolitica are discussed, with a review of the literature.